Pemanfaatan Digital Marketing Dalam Meningkatkan Penjualan Produk Umkm Di Indonesia - Ajeng Nisa; Dwi Novaria Misidawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Digital Marketing is currently widely used by the public as one of the media that supports a business. The approach used in this research is a qualitative approach. The purpose of this study is to analyze the effect of digital marketing utilization in increasing sales of MSMEs in Indonesia. This research is based on a literature study (Library Research). In this study, researchers used the observation method as a data collection method to obtain secondary data. The results of this study indicate that the use of social media for some MSMEs provides benefits, among others, as a means to communicate directly with customers, as a means of product promotion, collecting data on customer needs and desires, providing responses and input to consumers as a basis for decision making in transactions. MSMEs that have a competitive advantage have several characteristics such as good and quality human resources, optimal in utilizing technology, able to increase productivity and product quality, have a wide network and market reach, a structured management system, adequate capital and have an entrepreneurial spirit and an extensive business network. The conclusion of this study is that digital marketing has a significant effect on increasing sales of MSME products. The most widely used social media is E-Commerce. Facebook (FB), Instagram (IG) and Twitter, while whatsapp business is the main media for communication/chat with customers. The most perceived benefit is that communication with customers and suppliers is more intensive and effective and efficient, because it can communicate directly for 24 hours / real time. The transaction process is easier and cheaper because the communication media only incurs credit costs to support communication